Stock investments for old-age: Less return, more risk, and unexpected timing - Dirk Ulbricht (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Returns merely based on one purchasing price of an asset are uninformative for people regularly contributing to their old-age provision. Here, each purchase has an influence on the outcome. Still, they are commonly used in finance literature, giving an overly optimistic view of expected long-term stock market returns and risks. Moreover, around business cycle turning points when volatility is high, these differences are accentuated so that the timing of market entries and exists differ substantially. This article compares risk and returns for regular and lump-sum investors for all possible intervals of investments in the Dow Jones Industrial Average ranging from one to 480 months from January 1934 to April 2013. Moreover, the optimal timing for the two types of investors in the run-up to business cycle turning points are contrasted. Lump-sum returns for forty year-horizons overstate regular contributors yields by 1.4 percentage points implying a forty percent higher terminal value. The Sharpe ratio of lump-sum investments is about 260 percent higher than for regular contributors, and the risk of negative returns disappears for horizons that are six years shorter. Increasing contributions deteriorate risk and returns. While lump-sum investors have eight months more time to switch to riskless assets before a contraction, regular contributors may return five months earlier to the stock market than lump-sum investors.
Keywords: G11; G10; E44; 330; Retirement accounts; Risk and return; Business cycle; Investment management; Dollar-Cost Averaging